EVALUATION OF THE EFFECT OF NOREPINEPHRINE ON HEMODYNAMIC PARAMETERS IN RIGHT VENTRICULAR FAILURE AFTER CARDIAC SURGERY IN CHILDREN (Herald of the National Children's Medical Center, 2025)
Tetrad of Fallot is a complex congenital heart defect requiring surgical intervention. After RCTF, patients are at risk of developing right ventricular failure, which necessitates the optimization of inotropic support. Right ventricular failure (RVN) remains one of the key complications after radical correction of the Fallot Tetrad (RCTF). This article examines the effect of norepinephrine on hemodynamic parameters of patients with PHN after RCTF.